The relationship between childhood Injury and family type - Stokes, M; Higgins, D; Richardson, N; Bromfield, L; Tooley, G (My University, 2005)
Using data on the 4-5 year old children participating in the Growing Up in Australia study, this examination of the relationship between family structure and incidence of child injury indicates that children in sole parent families, but not in stepfamilies, were over represented among the 17 percent of children who sustained an injury. Although children living in sole parent and step families have a slightly higher injury rate than those in intact families, this slightly higher injury risk could be fully explained by the higher levels of socioeconomic disadvantage in sole parent households. It is likely that any higher risk for child injury in non intact families occurs because such families are more likely to possess child, parent, family and neighbourhood characteristics that are risk factors for child injury, rather than being specific to family type itself.
Keywords: Health; Health -- Injury; Families; Families and relationships; Health and wellbeing; Health; Families; Injury; Families and relationships; Health and wellbeing